ضوابط الكسب الحلال عبر المنصات الرقمية: دراسة فقهية تحليلية في عصر اقتصاد المنصات: Limitations of Making a Halal Livelihood through Digital Platforms: An Analytical Fiqh Study in the Platform Economy Era - Itsnaini Bambang Hasto Nugroho; Isman Isman (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This research aims to explore the sharia principles that govern economic activities in the "Platform Economy", which has become a key pillar in the contemporary global financial system. The problem of this research arises from the rapid development of digital business models and their relationship with the alleged gharar (obscurity), jahalah (ignorance), and usury, which requires the renewal of fiqh in accordance with these developments. This study uses a descriptive approach to analyze the working mechanism of the platform, as well as a deductive analytical approach to apply general fiqh rules to emerging digital problems. This study concludes that the profits obtained through digital platforms are subject to basic principles, the most important of which are: the halalness of objects (services or goods), the transparency of contract algorithms to avoid jahalah, and the application of sharia rules in the legal control of digital assets. The study also emphasizes that the determination of fiqh platforms often falls between the status of brokers and paid agents, which requires regularity in formulating "terms of use" to ensure fairness in financial distribution. This research recommends the need for an international charter of ethics and sharia for digital platforms to strengthen the digital Islamic economy.